2017
DOI: 10.1080/13607863.2017.1399341
|View full text |Cite
|
Sign up to set email alerts
|

Supporting family dementia caregivers: testing the efficacy of dementia care management on multifaceted caregivers’ burden

Abstract: Our findings support evidence for the effectiveness of DCM to lower family dementia caregivers' burden in multifaceted dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 21 publications
1
37
0
2
Order By: Relevance
“…5 Institute of Medical Psychology and Medical Sociology, University Medicine Rostock, Rostock, Germany. 6 Department of Psychiatry and Psychotherapy, University Medicine Greifswald, Greifswald, Germany.…”
Section: Fundingmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Institute of Medical Psychology and Medical Sociology, University Medicine Rostock, Rostock, Germany. 6 Department of Psychiatry and Psychotherapy, University Medicine Greifswald, Greifswald, Germany.…”
Section: Fundingmentioning
confidence: 99%
“…Specifically, previous research revealed that caring for a PwD is particularly burdensome due to the irreversible and progressive nature of the disease, its long duration, and the deterioration in multiple areas of cognitive abilities, behavior, and personality [4]. Current research specified that the confrontation with cognitive impairment and behavioral symptoms (i.e., aggression and personality changes), and the need to assist in activities of daily living, are especially burdensome and distressing for caregivers [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most people with dementia live at home and are cared for primarily by their spouse or adult children, the informal caregivers [ 2 ]. Caring for people with dementia is perceived as one of the most stressful experiences, as family caregivers may face long-term problems of managing activities of daily living [ 3 , 4 ], behavioral and psychological symptoms [ 5 , 6 ], and organizing care and providing emotional support [ 7 , 8 ]. However, due to a lack of supportive resources and knowledge of dementia, family caregivers have low confidence in managing caregiving [ 9 ] and do not know what to do when their relatives have dementia-related behavioral problems, need emotional support, and require the coordination of dementia care [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, providing care to a person with dementia can risk high physical, psychological, emotional and social impact on caregivers. The RCT carried out by Zwingmann et al (2017) showed that a dementia care management intervention can be effective to decrease caregivers' objective burden due to caring, subjective burden due to behavior change and perceived conflicts between needs and responsibilities to care compared to a control group receiving care as usual. The authors found that even small to medium effects might help to decreases the risk of health impairments and raise satisfaction, engagement and personal growth in caregivers.…”
Section: Advancing Dementia Researchmentioning
confidence: 99%